Assessing quality in postsecondary education : international perspectives - Weingarten, Harvey P., 1952-; Hicks, Martin, 1957-; Kaufman, Amy, 1977- (Queen's policy studies., 2018)
"For many years the benefits conferred by a higher education went undisputed. But students, employers, governments, and taxpayers are now demanding evidence of educational quality and value. At the same time, fiscally strapped governments are raising questions about how institutions are funded and the role quality should play in setting funding levels. In the face of these mounting pressures, jurisdictions around the world are working toward designing meaningful indicators to measure the performance of postsecondary institutions that go beyond enrolment numbers, graduation rates, and ever-popular reputational rankings. Assessing Quality in Postsecondary Education: International Perspectives presents a collection of thought-provoking essays by world-renowned higher-education thinkers and policy experts that discuss ways of defining and measuring academic quality. The papers were presented at a conference convened by the Higher Education Quality Council of Ontario in May 2017 and provide valuable insight into this pressing issue and underscore the need for reform"--Page 4 of cover.